Family Health Expenditure after Liberalisation : Kerala Experience - T P Kunhikannan K P Aravindan (Economic and Political Weekly January 13-20, 1996, 1996)
A study of household expenditure covering a small hut representative sample over the last four years shows that medical expenditure has risen sharply. Is this the effect of privatisation?